Adeline Ravoux, By Vincent Van Gogh, Cleveland Museum Of Art, 1958.31 - Vincent van Gogh (NC, 2026)
In May 1890, Van Gogh left the south and settled in Auvers, a small town north of Paris, where he rented a room at the inn of Arthur Ravoux. This portrait, completed during the last months of the artist’s life, depicts Ravoux’s 13-year-old daughter, Adeline. Van Gogh wrote that rather than photographic resemblance, he wanted his portraits to convey the “impassioned aspects” of contemporary life through the “modern...
Droits : Licence indiquee par Wikimedia Commons
Keywords: oeuvre d'art; musee; Van Gogh; Art